Zinc oxide nanoparticles improved chlorophyll contents, physical parameters, and wheat yield under salt stress - Adil, Muhammad; Bashir, Safdar; Bashir, Saqib; Aslam, Zubair; Ahmad, Niaz; Younas, Tasaddaq; Asghar, Rana Muhammad Ammar; Alkahtani, Jawaher; Dwiningsih, Yheni; Elshikh, Mohamed S. (Frontiers in Plant Science, 2022)
Nanotechnology has wide range of applications. Nanotechnology refers to the particle in nano scale used to improve agricultural productivity and to encounter the problems unsolved conventionally. Nanostructured formulation through mechanisms such as targeted delivery or slow/controlled release mechanisms as well as conditional release, could release their active ingredients in response to the environmental conditions and biological demands more precisely. Nanotechnology has a great potential for achieving sustainable agriculture, especially in developing countries. Salinity is among the major abiotic stresses which limits the yield and quality of global crops. Zinc (Zn) is a vital micronutrient that is mandatory for ideal growth of plants and has proved to reduce the hazardous effects of salt stress. To counter salinity problem, a pot experiment was conducted at wire house, institute of soil and environmental sciences (ISES), university of agriculture, Faisalabad, Pakistan to observe the effects of zinc oxide ZnO nanoparticles (ZnO NPs) on wheat variety ‘Gemmieza’ imported from Egypt under salt stress. 10 dS/m salinity was developed artificially and different doses of Zn conventional fertilizer and ZnO NPs were applied to potted wheat. ZnO NPs (0.12 g/pot) significantly increased physical parameters of wheat compared to control under salt stress. Application of ZnO NPs (0.12 g/pot) significantly increased chlorophyll A and B contents by 24.6 and 10 %, plant height at vegetative and maturity stages by 34.6 and 37.4 %, shoot and spike lengths by 30.7 and 27.6 %, root fresh and dry weights by 74.5 and 63.1 %, and wheat grain yield by 42.2 %, respectively. ZnO NPs performed better compared to Zn conventional fertilizer under salt stress and could be used in place of Zn conventional fertilizer in salt affected soils for attaining better crop production.